The Effectiveness of Inclusion Curriculum In Meeting The Needs of Diverse Students - Sholeh , Muh Ibnu (CV Kalimasada Group, 2024)
Abstract: Inclusive education has become a major focus in various countries in efforts to ensure accessibility, equality and justice in education for all individuals regardless of differences. Factors that influence the effectiveness of an inclusive curriculum include support from various stakeholders, teacher knowledge and skills, and challenges in assessing student progress. This research uses the library research method. This data source can be obtained through various sources, both offline and online. Researchers search for related literature sources using online databases such as Google Scholar, ResearchGate, Publish or Perish, WOS, Beliefe search engines and JSTOR, data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this research show that the active and collaborative role of government, schools, teachers, parents and society is very important in creating an inclusive learning environment . Teachers who are well trained in inclusive teaching strategies are crucial to the success of inclusive education. However, challenges remain in assessing the effectiveness of inclusive curricula, which requires evaluations that take into account students' individual needs and flexible evaluation approaches. Thus, further research is needed to understand more deeply the effectiveness of inclusive curricula and improve inclusive education practices overall.